Productive transformation in Amazonian value chains: The role of multi-stakeholder governance in the Brazil nut value chain in Madre de Dios (Peru) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2026)
This study examines the role of multi-stakeholder governance in structuring sustainable productive transformation strategies within the Brazil nut value chain in Madre de Dios, Peru. Despite growing interest in sustainable value chains and Amazonian bioeconomy, limited attention has been paid to how collaborative governance mechanisms shape productive transformation processes in non-timber forest product systems characterized by high institutional fragmentation and territorial complexity.Using a qualitative case study approach, the research integrates documentary analysis, semi-structured interviews with key stakeholders, and participatory validation processes conducted during the formulation of the Brazil Nut Roadmap 2030. The analysis is structured around five interrelated dimensions: governance and institutional articulation, productive and technological capacities, innovation and value addition, social inclusion, and environmental sustainability.The findings show that the Brazil Nut Roadmap operates not only as a planning instrument but also as a mechanism for territorial coordination and consensus-building among public institutions, private actors, producer organizations, and international cooperation agencies. The study identifies persistent structural constraints related to productive capacities, commercialization, technological upgrading, and institutional coordination, while also highlighting opportunities linked to value addition, bioeconomy strategies, sustainability-based differentiation, and access to specialized markets.The paper argues that productive transformation in Amazonian value chains depends not only on technological improvements, but also on the existence of collaborative governance arrangements capable of coordinating actors, mobilizing institutional capacities, and aligning long-term territorial development agendas. In this sense, the study contributes to the literature on sustainable value chains and territorial governance by providing empirical evidence on how multi-stakeholder articulation can support sustainable productive transformation processes in Amazonian contexts.
Keywords: Brazil nut; Amazon nut; multi-stakeholder governance; productive transformation; global value chains; industrial policy; Bioeconomy; non-timber forest products; sustainable territorial development; Peru